Last Screens of Malaya: Preserving the Traditional Wayang Pacak through Documentaries - Lee, Yuen Beng; Anuar, Mohd Firdaus Mohd; Kai, Liew Kah; Zainuddin, Maslisa; Ismail, Zuhaili Akmal; Santano, Delas; Peter, Jerry Tan; Gnana Selvan Edward (Journal of Ecohumanism, 2025)
In recent decades, cultural heritage and archiving have become vital for preserving and making heritage more accessible. Improving techniques for preservation is essential for safeguarding a country’s intellectual and economic wealth, enabling better conservation, cost savings, and wider distribution. Cinema, as both physical and intangible cultural property, plays a key role in this process through research-creation, which combines art, theory, and research. This approach also allows documenting intangible cultural heritage, challenging traditional methods by focusing on audience experiences, screening schedules, exhibition formats, and film reception. This paper is the first to discuss Malaysia’s traditional 35mm Wayang Pacak using SDG Target 11.4—protecting the world’s cultural and natural heritage—as its framework. It offers insights into the socio-cultural influences, technical evolution, historical development, and characteristics of Wayang Pacak using archival research and case studies. Additionally, it examines the collaborative research-creation process involving academics, filmmakers, and sound specialists in documentary production. Ultimately, this project aims to celebrate and preserve the Wayang Pacak, sharing it with both local and global audiences.